2014
DOI: 10.1542/peds.2013-3990
|View full text |Cite|
|
Sign up to set email alerts
|

Longitudinal Profiles of Adaptive Behavior in Fragile X Syndrome

Abstract: WHAT'S KNOWN ON THIS SUBJECT: To date, studies of adaptive behavior in fragile X syndrome have focused on particular age points, either longitudinally or cross-sectionally across a broad age spectrum. Studies have shown variable patterns in adaptive behavior among people with fragile X syndrome. WHAT THIS STUDY ADDS:This study fills a critical gap in knowledge about the profile of adaptive behavior across childhood, adolescence, and young adulthood in fragile X syndrome. This study is the first to incorporate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(99 citation statements)
references
References 27 publications
4
94
1
Order By: Relevance
“…Standard scores on the Vineland Adaptive Behavior Scale for overall adaptive behavior as well as subdomains have also been shown to decline with age during childhood, in males more so than in females with FXS [14]. Decline in standard scores for intelligence and adaptive function is not the results of loss of skills or regression but rather failure to keep pace with the normal rate of intellectual development.…”
Section: Cognitive Behavioral and Language Features Of Fxsmentioning
confidence: 99%
“…Standard scores on the Vineland Adaptive Behavior Scale for overall adaptive behavior as well as subdomains have also been shown to decline with age during childhood, in males more so than in females with FXS [14]. Decline in standard scores for intelligence and adaptive function is not the results of loss of skills or regression but rather failure to keep pace with the normal rate of intellectual development.…”
Section: Cognitive Behavioral and Language Features Of Fxsmentioning
confidence: 99%
“…While full analyses are pending, preliminary findings showed that many areas of positive response have not been well captured by the primarily parent-based outcome measures; thus, we are seeing only part of response. Arbaclofen 1 year (Vineland) data that showed change in the FXS disease trajectory in terms of participant adaptive skill has much relevance given that longitudinal have shown that the acquisition of adaptive skills slows, especially in male, as individuals with fragile X syndrome age [108].…”
Section: Discussionmentioning
confidence: 99%
“…It is hoped that future research efforts will evaluate these intensive early intervention strategies in children with FXS, perhaps in combination with pharmacological approaches. A recent large-scale longitudinal study of adaptive behavior profiles shown by individuals with FXS over childhood to adulthood indicated that the most meaningful improvements in daily living skills occurred after 14 years of age (Klaiman et al, 2014). These data indicate that the developmental period from childhood to early adolescence is critical and that intervention strategies that address autistic symptomatology (and underlying symptoms of social anxiety) in FXS during this period are sorely needed.…”
Section: Discussionmentioning
confidence: 99%